Increased survival rates in gastric cancer, with a narrowing gender gap and widening socioeconomic status gap: A period analysis from 1984 to 2013. Issue 4 (6th February 2018) - Sun, Fengze; Sun, Huanhuan; Mo, Xiangqiong; Tang, Jianjun; Liao, Yifeng; Wang, Shuncong; Su, Yonghui; Ma, Haiqing
Abstract: Background and Aim: Gastric cancer (GC) has the fifth highest incidence rate of all cancers and has a poor prognosis. However, no recent large‐scale and long‐term studies have evaluated the incidence and survival rates of individuals with GC. Methods: In order to explore the change of GC incidence and survival rates by age, gender, race, and socioeconomic status (SES), incidence data and survival status of patients with GC between 1984 and 2013 were abstracted from the Surveillance, Epidemiology, and End Results database. Totally, 87 242 cases of GC were exported and were analyzed. Results: During these three decades, the incidence of GC was 7.4, 6.8, and 5.5 per 100 000 individuals in each decade. The 1‐year relative survival rates (RSRs) improved from 42.4% to 44.3% to 49.0% ( P  < 0.0001), with a larger increase seen in the third decade. However, the long‐term survival rates remained low (from 17.8% to 20.3% to 22.9% for the 5‐year RSRs, P  < 0.0001; from 14.1% to 16.4% to 18.6% for the 10‐year RSRs, P  < 0.0001). Conclusion: Our analysis demonstrated the decreased incidence and increased survival rate of GC. In addition, lower SES was associated with lower survival rates. It is notable that others (primarily for Asians) had the highest incidence rate but had better outcomes than Whites and Blacks.